Methodological proposal for the evaluation of the ethical quality of the news about violence against women (Communication & Society, 2017)
Over the last decades there has been a significant increase in the academic literature focused on the journalistic approach about violence against women in Spain. However, and despite the wide-ranging recommendations on how to tackle this challenge in information, there is no tool that gathers and explains the ethical criteria and helps journalists in their work of drafting a news release. On the basis of what is known as quality journalism, this paper studies the different existing documents on codes of conduct in order to develop an analytical tool which assesses the quality of news concerning violence against women. The potential of this tool lies, among other issues, in the capacity to evaluate, both before and after, the ethical appropriateness to the public consensus so as to enhance the communication of this problem to the public and, thereby, contribute to stop it.